Polyionic polymers – heterogeneous media for metal nanoparticles as catalyst in Suzuki–Miyaura and Heck–Mizoroki reactions under flow conditions - Mennecke, Klaas; Kirschning, Andreas (Beilstein Journal of Organic Chemistry, 2009)
The preparation of monolithic polyionic supports which serve as efficient heterogeneous supports for palladium(0) nanoparticles is described. These functionalized polymers were incorporated inside a flow reactor and employed in Suzuki–Miyaura and Heck cross couplings under continuous flow conditions.
Keywords: Heck–Mizoroki reaction; heterogeneous catalysis; ion exchange resin; microreactor; monolith; palladium; Suzuki–Miyaura reaction